2008 4th International Conference on Wireless Communications, Networking and Mobile Computing 2008
DOI: 10.1109/wicom.2008.1180
|View full text |Cite
|
Sign up to set email alerts
|

Service Discovery Architecture Based on IMS for Future NGN

Abstract: IP Multimedia Subsystem (IMS) realizes the convergence of fixed and mobile networks. In virtue of providing various types of multimedia services among different kinds of access networks, IMS is considered as the core network for future Next Generation Networks. For detecting the requested services quickly and efficiently, it is necessary for IMS to adopt a valid Service Discovery function. In this paper, we propose a novel Service Discovery Architecture (SDA) to support a universal Service Discovery function i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…[2] capable of locating services in wide and local area networks [44] suggest GloServ provide little control on the service information exchanged between networks. [29] It uses XML to describe the services and queries and can preserve expressiveness of the services [47] have shown that the approach cannot be adapted across multiple networks that require access. [24] Maximizes efficiency and sustainability of deployments, Provides search engine capability to suit the integration of distributed resources repositories, Offer support for context-aware and location data [46] suggest it is centralised and did not take into account adaptivity to different network environments.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…[2] capable of locating services in wide and local area networks [44] suggest GloServ provide little control on the service information exchanged between networks. [29] It uses XML to describe the services and queries and can preserve expressiveness of the services [47] have shown that the approach cannot be adapted across multiple networks that require access. [24] Maximizes efficiency and sustainability of deployments, Provides search engine capability to suit the integration of distributed resources repositories, Offer support for context-aware and location data [46] suggest it is centralised and did not take into account adaptivity to different network environments.…”
Section: Acknowledgmentsmentioning
confidence: 99%